2018
DOI: 10.1007/s00784-018-2509-8
|View full text |Cite
|
Sign up to set email alerts
|

One-year clinical evaluation of bulk-fill flowable vs. regular nanofilled composite in non-carious cervical lesions

Abstract: Both bulk-fill flowable and regular nanofilled composites showed good clinical performances for the restoration of NCCLs after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 43 publications
1
32
0
8
Order By: Relevance
“…In all included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the number of patients ranged from 22 to 86, with a follow-up time of between 6 months and 10 years. The countries, where the studies were carried out were: Turkey [ 14 , 16 , 18 , 20 , 27 ], Brazil [ 22 , 23 , 25 ], Germany [ 21 , 26 ], Sweden [ 17 , 19 ], Denmark [ 19 ], and Saudi Arabia [ 24 ]. Ten studies [ 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 ] reported that the mean age of the patients was between 7.41 and 55.30 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the number of patients ranged from 22 to 86, with a follow-up time of between 6 months and 10 years. The countries, where the studies were carried out were: Turkey [ 14 , 16 , 18 , 20 , 27 ], Brazil [ 22 , 23 , 25 ], Germany [ 21 , 26 ], Sweden [ 17 , 19 ], Denmark [ 19 ], and Saudi Arabia [ 24 ]. Ten studies [ 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 ] reported that the mean age of the patients was between 7.41 and 55.30 years.…”
Section: Resultsmentioning
confidence: 99%
“…The countries, where the studies were carried out were: Turkey [ 14 , 16 , 18 , 20 , 27 ], Brazil [ 22 , 23 , 25 ], Germany [ 21 , 26 ], Sweden [ 17 , 19 ], Denmark [ 19 ], and Saudi Arabia [ 24 ]. Ten studies [ 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 ] reported that the mean age of the patients was between 7.41 and 55.30 years. Three studies [ 14 , 27 , 28 ] reported that the patients were children or under 18 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations